Cover Picture: Evaluating p97 Inhibitor Analogues for Potency against p97–p37 and p97–Npl4–Ufd1 Complexes (ChemMedChem 9/2016). (3rd May 2016) - Gui, Lin; Zhang, Xiaoyi; Li, Kelin; Frankowski, Kevin J.; Li, Shan; Wong, Daniel E.; Moen, Derek R.; Porubsky, Patrick R.; Lin, Henry J.; Schoenen, Frank J.; Chou, Tsui‐Fen
Abstract : The front cover picture shows p97 as it forms complexes with three different p97 cofactors. Each complex is unique and can be targeted by small molecule inhibitors. P97 performs multiple cellular functions, such as ubiquitin‐proteasome‐dependent degradation, endoplasmic‐reticulum‐associated degradation, membrane fusion, and autophagy–with help from cofactor proteins. Inhibitors of p97 ATPase activity are potential anticancer agents, which are being developed for clinical use. Developing inhibitors for specific p97 complexes is an exciting challenge and will be critical for studying p97's biological functions, as well as targeting p97 complexes in cancer, to reduce unwanted cytotoxicity. More information can be found in the Full Paper by Tsui‐Fen Chou et al. onpage 953 in Issue 9, 2016 (DOI:10.1002/cmdc.201600036 ).